2020
DOI: 10.1088/1748-9326/abbd02
|View full text |Cite
|
Sign up to set email alerts
|

The CO2 reduction potential for the European industry via direct electrification of heat supply (power-to-heat)

Abstract: The decarbonisation of industry is a bottleneck for the EU’s 2050 target of climate neutrality. Replacing fossil fuels with low-carbon electricity is at the core of this challenge; however, the aggregate electrification potential and resulting system-wide CO2 reductions for diverse industrial processes are unknown. Here, we present the results from a comprehensive bottom-up analysis of the energy use in 11 industrial sectors (accounting for 92% of Europe’s industry CO2 emissions), and estimate the technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 37 publications
0
81
0
Order By: Relevance
“…Several studies have suggested the electrification of kilns and conversion of power to heat for clinker manufacturing [188][189][190][191][192][193]. Solar calciners have been discussed in Sect.…”
Section: Electricity and Hydrogen: Towards Carbon Neutrality Of Clay Calcinationmentioning
confidence: 99%
“…Several studies have suggested the electrification of kilns and conversion of power to heat for clinker manufacturing [188][189][190][191][192][193]. Solar calciners have been discussed in Sect.…”
Section: Electricity and Hydrogen: Towards Carbon Neutrality Of Clay Calcinationmentioning
confidence: 99%
“…Electrification increasingly pivotal for just sustainability transitions and urban areas are at the forefront Urban electrification has accelerated in recent years (World Economic Forum, 2020). However, although the decarbonization impacts of electrification are well documented in industrial and transport sectors (Alarfaj et al, 2020;Arabzadeh et al (2020); Lah et al, 2020;Madeddu et al, 2020;Mai et al, 2020), comprehensive analyses of the role that urban electrification can play are lacking (Fuso Nerini et al, 2019). The sustainable energy transition relies on a concurrent global urban transition (IRENA, 2019;IPCC et al, 2018).…”
Section: Economic Stimulus Focused Primarily On Growth Would Jeopardize the Paris Agreementmentioning
confidence: 99%
“…Studies of deep decarbonization pathways show that the power sector offers many opportunities for deep decarbonization by the middle of the century, including in China (Duan et al, 2021), making electrification vital (Victoria et al, 2020). Direct electrification is preferable as it increases efficiency (Madeddu et al, 2020), but hydrogen-based fuels could play a role where electrification is not feasible (Ueckerdt et al, 2021).…”
Section: Fig 2 Heading Towards Net-zero Co 2 Emissions and The 15°c Target The X-axis Shows Cumulativementioning
confidence: 99%